Mitochondrial permeability transition pore as a selective target for anti-cancer therapy - Suh, Dong Hoon; Kim, Mi-Kyung; Kim, Hee Seung; Chung, Hyun Hoon; Song, Yong Sang (Frontiers in Oncology, 2013)
Mitochondrial outer membrane permeabilization (MOMP) is the ultimate step in dozens of lethal apoptotic signal transduction pathways which converge on mitochondria. One of the representative systems proposed to be responsible for the MOMP is the mitochondrial permeability transition pore (MPTP). Although the molecular composition of the MPTP is not clearly understood, the MPTP attracts much interest as a promising target for resolving two conundrums regarding cancer treatment: tumor selectivity and resistance to treatment. The regulation of the MPTP is closely related to metabolic reprogramming in cancer cells including mitochondrial alterations. Restoration of deregulated apoptotic machinery in cancer cells by tumor-specific modulation of the MPTP could therefore be a promising anti-cancer strategy. Currently, a number of MPTP-targeting agents are under pre-clinical and clinical studies. Here, we reviewed the structure and regulation of the MPTP as well as the current status of the development of promising MPTP-targeting drugs.